Desenvolvimento e caracterização de nanocompósito de resina epóxi com nanopartículas de sílica para revestimento de dutos para transporte de petróleo - Mendonça, Rannier Marques (2009)
The use of polymer based coatings is a promising approach to reduce the corrosion problem in carbon steel pipes used for the transport of oil and gas in the oil industry. However, conventional polymer coatings offer limited properties, which often cannot meet design requirements for this type of application, particularly in regard to use temperature and wear resistance. Polymer nanocomposites are known to exhibit superior properties and, therefore, offer great potential for this type of application. Nevertheless, the degree of enhancement of a particular property is greatly dependent upon the matrix/nanoparticle material system used, the matrix/nanoparticle interfacial bonding and also the state of dispersion of the nanoparticle in the polymer matrix. The objective of the present research is to develop and characterize polymer based nanocomposites to be used as coatings in metallic pipelines for the transportation of oil and natural gas. Epoxy/SiO2 nanocomposites with nanoparticle contents of 2, 4, and 8 wt % were processed using a high-energy mill. Modifications of the SiO2 nanoparticles‟ surfaces with two different silane agents were carried out and their effect on the material properties were investigated. The state of dispersion of the materials processed was studied using Scanning and Transmission Electron Microscopy (SEM and TEM) micrographs. Thermogravimetric analysis (TG) were also conducted to determine the thermal stability of the nanocomposites. In addition, the processed nanocomposites were characterized by dynamic mechanical analysis (DMA) to investigate the effect of nanoparticles content and silane treatment on the viscoelastic properties and on the glass transition temperature. Finally, wear tests of the pin-on-disc type were carried out to determine the effects of the nanoparticles and the silane treatments studied. According to the results, the addition of SiO2 nanoparticles treated with silane increased the thermal stability, the storage modulus and Tg of the epoxy resin and decreased wear rate. This confirms that the interaction between the nanoparticles and the polymer chains plays a critical role on the properties of the nanocomposites